Dimensions of Ethical Behavior and Trends of Accounting Chain in Banking Industry of Small City - Baihaqi; Asmawanti-S, Dri (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to determine the effect of effectiveness of internal control, compensation compatibility, information asymmetry, and morality of management to unethical behavior and tendency of fraud accounting (study on banking companies in Bengkulu city). The data used in this research is primary data, obtained by distributing questionnaires to the respondents. The results prove that effectiveness of internal control, compensation compatibility, and morality of management have negative effect on unethical behavior. Effectiveness of internal control, compensation compatibility, and morality of management have negative effect on tendency of fraud accounting, but information asymmetry has no effect on unethical behavior and tendency of fraud accounting. Unethical behavior has positive effect on tendency of fraud accounting